Relational dialectics: researching change in intercultural families. Issue 1 (9th April 2020) - Rogan, Donal; Hopkinson, Gillian; Piacentini, Maria
Abstract : Purpose: This paper aims to adopt a relational dialectics analysis approach to provide qualitative depth and insight into the ways intercultural families manage intercultural tensions around consumption. The authors pay particular attention to how a relational dialectics analysis reveals a relational change in the family providing evidence to demonstrate how a family's unique relational culture evolves and transitions. Design/methodology/approach: Qualitative insights from a relational-dialectic analysis on 15 intercultural families are used to illustrate the interplay of stability with instability in the management of intercultural dialectic tensions within these families. Findings: Intercultural dialectical interplay around food consumption tensions are implicit tensions in the household's relational culture. Examples of dialectical movement indicating relational change are illustrated; this change has developmental consequences for the couples' relational cultures. Research limitations/implications: This study provides qualitative insights on relational dialectics in one intercultural family context and reveals and analyses the dialectical dimensions around consumption in the context of intercultural family relationships. The research approach could be considered in other intercultural and relational contexts. Practical implications: Family narratives can be analysed within the context of two meta-dialectics that directly address how personal relationships evolve; indigenous dialectic tensions within a family can also be identified. Originality/value: This paper demonstrates the qualitative value of a relational dialectics analysis in revealing how food consumption changes within families are the result of reciprocal or interdependent learning, which has consequences for relational change.